Outcome following resection of retroperitoneal sarcoma. Issue 13 (23rd September 2015) - Smith, H. G.; Panchalingam, D.; Hannay, J. A. F.; Smith, M. J. F.; Thomas, J. M.; Hayes, A. J.; Strauss, D. C.
Abstract : Background: Retroperitoneal sarcoma comprises a range of different histological subtypes with dissimilar behaviour and biology. This study sought to characterize the morbidity and mortality associated with multivisceral resection and oncological outcomes according to subtype. Methods: All patients undergoing resection of primary retroperitoneal sarcoma at the Royal Marsden Hospital between January 2005 and December 2014 were identified from a database. Results: Some 362 patients underwent resection, with 292 requiring multivisceral resection. The 30‐day mortality rate was 1·4 per cent (5 patients), the 30‐day morbidity rate was 15·7 per cent (57 patients), and 27 patients required a return to theatre. Age over 75 years was predictive of 30‐day mortality (hazard ratio 1·37, 95 per cent c.i. 1·13 to 1·65). The overall disease‐specific survival rate at 3 years was 81·2 per cent. For well differentiated liposarcoma, dedifferentiated liposarcoma and leiomyosarcoma, 3‐year local recurrence‐free survival rates were 98 (95 per cent c.i. 83 to 99), 56·7 (45·7 to 66·2) and 80 (67 to 89) per cent respectively. At 3 years the distant metastasis‐free survival rate was 100, 85·9 (77·4 to 91·4) and 65 (49 to 77) per cent, and the disease‐specific survival rate was 97 (89 to 99), 78·5 (74·6 to 82·4) and 79 (63 to 85) per cent for well differentiated liposarcoma, dedifferentiated liposarcoma and leiomyosarcoma respectively. Conclusion: Resection of retroperitoneal sarcoma was associated with a 30‐day mortality rate of less than 2 per cent and a morbidity rate of 15·7 per cent. The overall 3‐year disease‐specific survival rate was 81·2 per cent. Abstract : Treatment at specialized units is preferred